2018
DOI: 10.3390/separations5020023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment, Validation and Application to Real Samples of an RP-HPLC Method for the Determination of Guayulins A, B, C and D in Guayule Shrub

Abstract: Guayule (Parthenium argentatum Gray) is a shrub native to the arid regions of Mexico. In the last decades, significant attention to its cultivation has arisen because it is the raw material for the production of hypoallergenic natural rubber. Guayule biomass also contains high amounts of resin, which is not normally exploited in any way. Among other sesquiterpenic esters, guayulins (i.e., the parteniol esters of cinnamic acid, guayulin A, or of anisic acid, guayulin B) are contained in resin. In addition, mino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…During this study, the difficulty emerged when no commercial standards of guayulins were available. Those that had been used by other authors before were no longer available [1]. It was only possible to isolate guayulin A in our laboratory with enough purity to be considered as standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this study, the difficulty emerged when no commercial standards of guayulins were available. Those that had been used by other authors before were no longer available [1]. It was only possible to isolate guayulin A in our laboratory with enough purity to be considered as standard.…”
Section: Discussionmentioning
confidence: 99%
“…The guayulin family of sesquiterpene secondary metabolites comprises four known members, guayulin A-D [1,2], although several other members may exist [3,4]. Guayulin A was first isolated in 1911 and its structure was determined some years later [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Guayulins A and B have been shown to possess biological properties and to have a key role in the defense of the plant. They actually act as biological triggers in the synthesis of lychnostatine and paclitaxel, which are agents used in breast cancer treatment [ 113 , 114 ].…”
Section: Proposed Applications For Guayule-derived Productsmentioning
confidence: 99%
“…This is because guayulins C and D are often absent from freshly prepared acetone extracts [19] of guayule tissues. However, fresh extracts of leaves contained as much C and D as A and B, suggested that they were actively synthesized in the leaves, and not generated by oxidation post-extraction [21]. [19,22]).…”
Section: Guayulin Structurementioning
confidence: 99%
“…Although large quantities of guayulins can be found [19,21] and have potential applications as sesquiterpenes, there are few guayulin-specific reports in the scientific literature. Only 17 records were found in searchable databases (Web of Science, Scopus and PubMed) when the term "guayulin" is searched as relevant in title or abstract or keyword.…”
Section: Reported Guayule Resins or Its Components Activitymentioning
confidence: 99%